2003
DOI: 10.1051/limn/2003024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water removal on introduced caddisflies from a tropical mountain stream

Abstract: Similar changes to macroinvertebrate communities would be expected below dams and diversions of streams in other tropical regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
30
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 21 publications
7
30
3
Order By: Relevance
“…Other studies have shown that stream diversions lower overall habitat suitability for many native tropical species, also allowing for the invasion and successful colonization of certain introduced species (McIntosh et al, 2002(McIntosh et al, , 2003Brasher, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have shown that stream diversions lower overall habitat suitability for many native tropical species, also allowing for the invasion and successful colonization of certain introduced species (McIntosh et al, 2002(McIntosh et al, , 2003Brasher, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In regions such as Hawaii and neo-tropical regions that are subject to torrential, seasonal rainfall patterns, small running water systems are highly vulnerable to anthropogenic disturbances, yet continue to be overlooked (Flecker and Feifarek, 1994). The native gobies, shrimps and snails have received the most research attention in Hawaiian stream studies, with only a few recent on the macroinvertebrate communities (Kido, 1997a;McIntosh et al, 2002McIntosh et al, , 2003Benbow et al, 2003;Benbow et al, 2005). Macroinvertebrate communities can provide information on trophic changes that can have consequences for stream food web structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the benthic community structure were often assessed by examining taxonomic compositions along the stream continuum (Grubaugh et al 1996, González et al 2003. Spatial variations have been attributed to habitat characteristics (e.g., Brown 1984, Brown et al 1995, Boyero 2003, but also to stochastic temporal fluctuations of the environment (Ives & Kopfer 1997, McIntosh et al 2003. Based on the dynamic equilibrium concept (Curry 1972), streams form a balance between physical parameters (such as width, depth, velocity, and sediment load), and biological factors.…”
Section: Introductionmentioning
confidence: 99%
“…Within this framework, the persistence or elimination of a species thus depends on biological attributes (Townsend and Hildrew, 1994;Usseglio-Polatera et al, 2000), and on habitat characteristics McIntosh et al, 2003) respectively.…”
Section: Introductionmentioning
confidence: 99%